Evaluation of Effectiveness of Neonatal Resuscitation Programme (NRP) Course Among Paediatric Residents of BPKIHS - Yadav, SK; Bhatta, NK; Yadav, SP; Kanodia, P; Moktan, D (Journal of Nepal Paediatric Society, 2015)
Introduction: Neonatal resuscitation is an essential skill for neonatal care providers, especially for junior doctors who are often the first persons to attend to a newborn in need of resuscitation. The Neonatal Resuscitation Programme (NRP) training course offers a comprehensive and systematic training programme that has been adopted in 130 countries worldwide. Reports from different countries attributed the improvements in neonatal mortality and morbidity over the past two decades partly to the implementation of a systematic neonatal resuscitation training programme. The objective of this study was to evaluate the effectiveness of Neonatal Resuscitation Programme (NRP) in improving the knowledge of the paediatric resident doctors after completion of the course. Materials and Methods: This was a cross-sectional interventional study. The resident doctors who attended the NRP course were enrolled. The knowledge was evaluated by written 30-item questionnaire pre- and post- course score. Statistical analysis was done by descriptive statistics and paired t-test. p- value of <0.05 was taken as significant. Results: Data of 18 paediatric residents who attended the course were analyzed. There were four female and 14 male residents. Out of 18 residents, eight were from first year, seven were from second year and three were from third year. Their mean scores (out of 30) were 13.84 (SD 2.57) (pre-course) and 16.68 [(SD 3.15) (post-course) (p=0.001)]. Conclusions: NRP course produced a modest gain in residents’ knowledge on neonatal resuscitation at the end of their course. NRP training has the potential to substantially improve knowledge of neonatal resuscitation. J Nepal Paediatr Soc 2015;35(1):18-23